Environmental selection underlies distinct distribution patterns of closely related European evening primroses - Monika Woźniak-Chodacka; Maciej Kocurek; Maria Pilarska; Ewa Niewiadomska (Scientific Reports)
Abstract Understanding of species distribution is becoming a key concern in biogeography, ecology and evolution when to consider the ongoing climate change. This study investigates the distribution patterns of closely related Oenothera species focusing on their adaptations to environmental conditions through morphological traits and photosynthetic adjustments. We documented the three distinct distribution patterns in Europe among the studied species. Oenothera rubricaulis, found at higher latitudes, has the smallest flowers and the highest chlorophyll content, accompanied by anthocyanin accumulation, which maximizes light acquisition under low light conditions. Oenothera suaveolens, observed at lower latitudes, displays the largest flowers, a pure green phenotype, the highest stomatal conductance, and a light avoidance strategy, reflected by rapid photoinhibition and hyponasty. Oenothera biennis, with the widest distribution, exhibits an intermediate phenotype, suggesting high plasticity and adaptability of its photosynthetic apparatus. Given the close relationship of these species, our findings suggest that environmental selection following hybridization events has been crucial for their establishment in Europe.